The new process toward collaborative learning - Berka Belaghemas; Amal Mouterfi; Rachida Addad (Dirassat Journal Economic Issue, 2020)
Blended learning which is an integrated learning, combining the face-to-face and virtual learning, not only improves the training, but also questions and promotes the employee’s self-learning and collaboration skills. The most important innovation for organizations is the establishment of a new learning culture through online training, which is for everyone and which can be used by anyone whom is interested. In order to bring all the training participants, to the same level of knowledge before the presentation training, and to involve them more for more sharing. If comprehension problems arise, it is always possible to ask questions during the learning phase, time advancement during basic knowledge acquisition, offers more time for exercises during the presence phases and allows a targeted coaching performed by the trainers.